Originality, imitation, and plagiarism : teaching writing in the digital age - Eisner, Caroline, 1965-; Vicinus, Martha (University of Michigan Press, 2008)
This collection is a timely intervention in national debates about what constitutes original or plagiarized writing in the digital age. Somewhat ironically, the Internet makes it both easier to copy and easier to detect copying. The essays in this volume explore the complex issues of originality, imitation, and plagiarism, particularly as they concern students, scholars, professional writers, and readers, while also addressing a range of related issues, including copyright conventions and the ownership of original work, the appropriate dissemination of innovative ideas, and the authority and role of the writer/author. Throughout these essays, the contributors grapple with their desire to encourage and maintain free access to copyrighted material for noncommercial purposes while also respecting the reasonable desires of authors to maintain control over their own work.